PENGARUH STRES KERJA TERHADAP MOTIVASI KERJA DI POLITEKNIK KETENAGAKERJAAN SELAMA PENERAPAN WORK FROM HOME (WFH) - Hartanto; Ningrum, Tuti; Simanungkalit, Sarah W. (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this study was to determine the effect of work stress on employee motivation at the Manpower Polytechnic during the implementation of Work From Home (WFH). The type of research used is explanatory with a quantitative approach. Collecting data using a questionnaire with 58 respondents with a simple regression analysis method which produces a t count of -2.063, this shows that the value of t count is greater than t table (-2.063 > 2.003) and the significance value is less than 0.05 (0.04 < 0.05). which can be concluded that Ho is rejected and Ha is accepted. It can be interpreted if work stress has a negative and significant effect on work motivation (Y) during the implementation of Work From Home (WFH). Meanwhile, for the coefficient of determination of 0.071 which means that 7.1% of the work motivation variable (Y) can be explained by the work stress variable (X) while the remaining 92.9% can be explained by other variables not examined in this study.